Agile Governance Implementation through the DOLEN Program to Boost Reading Interest in East Java - Fierda Nurany; Bagus Ananda Kurniawan; Annastya Putri Kirana (Soshum: Jurnal Sosial dan Humaniora, 2024)
This research was conducted with the aim of finding out the extent of the application of Agile Governance principles during the Covid-19 pandemic to the East Java Provincial Library and Archives Service through the launch of the Online Fairy Tale Program (DOLEN). The researcher uses a qualitative approach with a type of descriptive research. The researcher conducted a data analysis based on the Agile Governance theory proposed by Luna et al, (2015). The researcher focuses on 3 (three) principles of Agile Governance. The results of this study show that the Online Fairy Tale Program (DOLEN) launched by the East Java Provincial Library and Archives Service which is regulated in the regulation of Law Number 43 of 2007 concerning Libraries has been effective in increasing reading interest, especially children and adolescents in East Java. This is seen from the achievement of 3 (three) principles that are used as indicators. In terms of Based On Quick Wins, the Online Fairy Tale Program (DOLEN) has been able to meet both the time and the program's goals. In terms of Systematic and Adaptive Approach, the relevant agencies have succeeded in adapting to the existing situation, especially during the Covid-19 pandemic, where all activities have switched to online-based, in addition to successfully synergizing with other regency/city libraries and resulting in replication. Then in the aspect of Symple Design and Continuous Refiniment, the selection of features or icons that are quite attractive and easy for users on the Instagram and Youtube or Facebook applications is one of the forms of innovation chosen by the government as a platform for online fairy tale activities (DOLEN).